Influencia do calcio na tolerancia do milho ¨Saracura¨ BRS-4154 ao encharcamento do solo - Magalhaes, Julio Cesar; Romero Ferrer, Jorge Luis; Donizeti Alves, José; Vasconcellos, Carlos Alberto; De Oliveira Cantao, Fernando Rodrigo (ABMS, 2018)
The Saracura maize BRS – 4154 was introduced as an alternative for swamp land areas subjected to temporary flooding. Evidences are usually obtained with CaCl2 presence in flooding germination buffer which increases the tolerance of Saracura. However, such experiments were carried out in controlled conditions, during germination and initial development phases of seedlings. There have been no papers, so far, showing the influence of calcium during the maize development cultivated at field conditions. Therefore, the objective of this research was to evaluate, during the vegetative and reproductive development of Saracura maize, the effect of different levels, sources and mode of calcium application in flooding conditions. For this purpose, this experiment conducted in field conditions. The following treatments were used: calcium sources and dosages (CaCl2 , 300.0 kg.ha-1 and gypsum, 500.0 and 1500.0 kg.ha-1) and ways of application (incorporated in the first 8.0 cm from surface, on the entire soil profile and on surface), in normal irrigation and under flooding conditions imposed at V6 growth stage throughout physiological maturity. A fully randomized block design with four replications was used, and the evaluations were accomplished at harvesting by analyzing traits related to growth and development, as well as yield and its components. Considering each environment it was not able to detect statistic differences among the variables, probably due the calcium content in soil which was sufficient for plant growth and development. However, when one compares characteristics between environments it was possible to detect higher effect from regular irrigation compared to flooding.